(untitled) (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2023)
As the main method of treatment, chemotherapy does not show high results, so it is used in combination with other measures. So, drug treatment is prescribed in the pre- and postoperative period, when regional lymph nodes are involved in the tumor process. The use of immunomodulators in the treatment of cancer patients in combination with routine methods of exposure remains a little studied issue. The results of the analysis of literature data on the use of immunomodulators in the complex treatment of cancer patients with small intestine cancer during chemotherapy are presented.